The use of electrodessication in the treatment of cutaneous neurofibromatosis: A retrospective patient satisfaction outcome assessment. Issue 6 (June 2016) - Lutterodt, C.G.; Mohan, A.; Kirkpatrick, N.
Summary: Introduction: Neurofibromatosis I (NF-1) is an autosomal dominant disease giving rise to hundreds of cutaneous neurofibromas. In addition to localised symptoms such as pain and pruritus, these lesions can have a devastating psychosocial impact. To date, there is no consensus on the optimal management of these lesions. We present the clinical and patient-reported outcomes of a series of NF-1 patients treated with electrodessication by one surgeon. Methods: All patients treated by electrodessication for cutaneous neurofibromas between 2012 and 2015 by one clinician were retrospectively reviewed. Clinical and patient-reported outcomes were measured using a patient satisfaction questionnaire and review of the notes. Results: Six patients were operated on during the study period (five women and one man). Prior to this new technique, patients had on average eight episodes (range 4–20) of excisional procedures under local anaesthesia removing one to five lesions. With electrodessication, patients had on average three (range 1–5) electrodessication episodes under general anaesthesia, treating hundreds of lesions per session. All patients were treated as a day case. One patient experienced a minor wound infection and another minor bleeding. Five of six patients preferred electrodessication to surgical excision. Conclusion: Electrodessication enables the treatment of hundreds of neurofibromas in a single operation. The procedure has low complication rates with high levels of clinical and patient-reported outcomes.